1999
DOI: 10.1890/0012-9658(1999)080[2358:cfbaco]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Foraging Behaviors Allow Coexistence of Two Consumers

Abstract: We developed a mathematical model based on the microalgal–gastropod system studied by Schmitt, in which two coexisting consumers (Tegula eisini and T. aureotincta) feed on a common resource. The two consumers differ in their foraging behavior and their ability to remove microalgae from rock surfaces. T. eisini is a digger, moving slowly and grazing the algae down to almost bare substrate, whereas T. aureotincta is a grazer, moving more quickly and leaving behind a larger fraction of the algal layer. These comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Given the uncertainty in the fitted parameters, the model predictions were not inconsistent with observed coexistence in the field (Schmitt 1996). In this article we have reviewed, generalized, and extended the work of Possingham (1987) and Wilson et al (1999) by investigating how the model of resource renewal affects coexistence.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Given the uncertainty in the fitted parameters, the model predictions were not inconsistent with observed coexistence in the field (Schmitt 1996). In this article we have reviewed, generalized, and extended the work of Possingham (1987) and Wilson et al (1999) by investigating how the model of resource renewal affects coexistence.…”
mentioning
confidence: 89%
“…Coexistence was dependent on the competitive ability of both species, which was defined as the mean net energy gained per calorie extracted from a flower, divided by the cost of using each flower. Wilson et al (1999) fitted a similar mathematical model, which described the dynamics of two benthic grazers competing for algae, to data collected by Schmitt (1996). Although the model required a number of parameters, the data were sufficient to give estimates to all parameters but one.…”
mentioning
confidence: 99%
“…However, in the mixed-grazer treatments I. emarginata in general showed a higher uptake of the labelled algal material as H. ulvae. Many studies in community ecology have tried to analyse the eVects of complementary feeding and coexistence on the resource use of competitors (Rossi et al 1983;Wilson et al 1999). In our study, interspeciWc competition appeared to induce a shift in assimilation eYciency leading to a stronger uptake of the algal material by I. emarginata.…”
Section: Algal Biovolumementioning
confidence: 99%
“…Many studies in community ecology have investigated the eVect of coexistence on the resource use of competitors and demonstrated that complementary feeding facilitates coexistence (Ricklefs and Schluter 1993;Wilson et al 1999). In our study interspeciWc competition appeared to induce a passive shift in feeding preference and in resource use by I. emarginata in the presence of H. ulvae.…”
Section: Faecal Pelletsmentioning
confidence: 99%
See 1 more Smart Citation